Pendampingan Digital Marketing untuk Meningkatkan Penjualan BUMDes Makmur Anugerah Lestari di Ciomas - Fatikhah, Sabna Ainazah; Yolanda, Ledy; Sudaryanto, Muhammad Adam; Manggarani, Cynthia Ayu (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Makmur Anugerah Lestari Village-Owned Enterprise (BUMDes), which oversees various business units and micro, small, and medium enterprises (MSMEs) in Sukamakmur Village and its surrounding areas, continues to face challenges in marketing strategies, as most MSME actors still rely on conventional methods that are less effective in reaching broader markets. Through a Community Service Program (PKM), a team from the Faculty of Economics and Business, Universitas Terbuka, conducted training and mentoring on digital marketing to strengthen the capacity of BUMDes and its assisted MSMEs. The program focused on enhancing the participants’ skills in utilizing digital technologies, developing promotional strategies through social media, and marketing products via e-commerce platforms. The training was conducted using a participatory approach, combining material delivery, hands-on practice, technical assistance, monitoring, and evaluation. The results of the program indicated an improvement in participants’ understanding of digital marketing concepts and their ability to implement online marketing strategies more effectively.